2020
DOI: 10.3390/en13133322
|View full text |Cite
|
Sign up to set email alerts
|

Non-Cooperative Game in Block Bidding Markets Considering Demand Response

Abstract: With the reform of electricity markets, demand response (DR) plays an important role in providing flexibility to the markets. Block bidding market is a new market mode, which is based on the concept of “the same quality, the same price”. The mechanism has great effects in reducing start-stop related costs. In this paper, we propose a double-sided non-cooperative game model in block bidding markets with a DR program. The model combines the advantages of block bidding and the simplicity of hourly bidding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…By applying the model to a hypothetical case example, the authors have demonstrated the superiority of their proposed model to the business-as-usual approaches in terms of maximising social welfare. In a marked departure from the existing literature, Guo et al [47] go further and apply their proposed method to DR-integrated block bidding markets, where the total electricity demand is divided into multiple blocks and the auction is processed block by block, each with an individual market-clearing price, in contrast to the traditional hourly pricing model. Similarly, Golmohamadi et al [48] have formulated a multi-agentbased scheduling framework for trading residential and industrial flexibility procured through DRAs in electricity markets.…”
Section: Game-theoretic Models Applied To Demand-side Management Studiesmentioning
confidence: 99%
“…By applying the model to a hypothetical case example, the authors have demonstrated the superiority of their proposed model to the business-as-usual approaches in terms of maximising social welfare. In a marked departure from the existing literature, Guo et al [47] go further and apply their proposed method to DR-integrated block bidding markets, where the total electricity demand is divided into multiple blocks and the auction is processed block by block, each with an individual market-clearing price, in contrast to the traditional hourly pricing model. Similarly, Golmohamadi et al [48] have formulated a multi-agentbased scheduling framework for trading residential and industrial flexibility procured through DRAs in electricity markets.…”
Section: Game-theoretic Models Applied To Demand-side Management Studiesmentioning
confidence: 99%